Use of national currencies for trade settlement in East Asia: A proposal - ll Houng Lee; Yung Chul Park (Asian Development Bank Institute (ADBI), 2014)
This paper develops a multilateral currency system where national currencies are used for trade settlement in East Asia, comprising the Association of Southeast Asian Nations (ASEAN) member countries, the People's Republic of China, Japan, and the Republic of Korea (ASEAN+3). The currency scheme is expected to mitigate the risks associated with independent attempts at internationalization in non-convertible currency countries. It could also reduce dependence on the US dollar, safeguard against financial spillovers from outside, and deepen trade and financial integration in the region. The patterns and structure of trade and financial openness suggest that East Asia has already established an economic base upon which it could launch such a system. The experience with renminbi internationalization will help the Republic of Korea and ASEAN-5 to emulate this strategy.
Keywords: F15; F36; F42; 330; currency internationalization; RMB internationalization; trade invoicing and settlement